1991
DOI: 10.2466/pr0.1991.68.3c.1323
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Familial Style and Creative Potential of Preschool Children

Abstract: The relationship between familial style and creative potential in preschool children was explored with a sample of 32 children (17 girls, 15 boys) and their parents. The children's ages ranged from 36 to 61 months ( M = 51). The children were given the Multidimensional Stimulus Fluency Measure as an assessment of creative potential. Parents completed FACES III, a measure of family interaction patterns. Analysis yielded a positive though nonsignificant r of .32 between FACES adaptability and total fluency of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Bomba & Moran, 1991;Csiksentmihalyi, 1996;Michel & Dudek, 1991;Olszewsk et al, 1987;OlszewskiKubilius, 2000;Simonton, 1984Simonton, , 1988Simonton, , 2000Walberg, 1988) and empirical findings (Yeh, 1999(Yeh, , 2000, I have determined two dimensions with respect to family factors that are important for the development of technological creativity: (a) model setting and support: parents and siblings act as models during the creative process; parents give opinions and guidance while children are in the process of problem-solving; parents encourage independence and autonomy; and (b) open atmosphere: the family atmosphere is free and open; parents support their childrens' decision-making; and good parent-child relationships exist. As mentioned earlier, the mesosystem consists of the family and school experiences; thus, these factors obviously represent the subsystem of the family unit.…”
Section: The Family and Technological Creativitymentioning
confidence: 97%
See 1 more Smart Citation
“…Bomba & Moran, 1991;Csiksentmihalyi, 1996;Michel & Dudek, 1991;Olszewsk et al, 1987;OlszewskiKubilius, 2000;Simonton, 1984Simonton, , 1988Simonton, , 2000Walberg, 1988) and empirical findings (Yeh, 1999(Yeh, , 2000, I have determined two dimensions with respect to family factors that are important for the development of technological creativity: (a) model setting and support: parents and siblings act as models during the creative process; parents give opinions and guidance while children are in the process of problem-solving; parents encourage independence and autonomy; and (b) open atmosphere: the family atmosphere is free and open; parents support their childrens' decision-making; and good parent-child relationships exist. As mentioned earlier, the mesosystem consists of the family and school experiences; thus, these factors obviously represent the subsystem of the family unit.…”
Section: The Family and Technological Creativitymentioning
confidence: 97%
“…As for parent-child interactions, research findings (Michel & Dudek, 1991) indicated that the avoidance of over protection and intervention, combined with the reception of more love and encouragement, strongly contribute to children's creativity. Moreover, a constructive family atmosphere-such as having flexibility in the family structure, caring about family members, trusting and supporting each other, having chances to express feelings, and thinking highly of cultural and intellectual activities-serves well in the development of creative potential (Bomba & Moran, 1991;Olszewski, Kulieke, & Buescher, 1987).…”
Section: The Family and Technological Creativitymentioning
confidence: 99%
“…As far as we are aware, our study was the first to test how parents’ creativity predicts such a comprehensively operationalized family lifestyle. Previous studies focused on one of these specific areas, namely either on the social context of family functioning [ 82 , 83 , 84 ], or on the climate for creativity built in the home environment [ 14 , 32 ]. Moreover, the relationship between parents’ creative self-efficacy and their behaviors that may support their offspring’s creativity has not yet been analyzed, while its importance seems natural.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study on preschool children’s creative potential and family social functioning demonstrated that children from more flexible families had slightly higher scores on originality, while children from more cohesive (enmeshed) families were less likely to score high on creativity measures [ 83 ]. However, high family cohesion was also a positive predictor of perceived own creativity among gifted Chinese students [ 84 ].…”
Section: Introductionmentioning
confidence: 99%